Paradigma Hakim Atas Perlindungan Hukum Anak Luar Kawin Kajian Putusan Mahkamah Konstitusi Nomor 46/PUU-VII/2010 - Erikson Sihotang (Jurnal Ilmiah Raad Kertha, 2019)
Article 28b paragraph (2) of the 1945 Constitution provides that "every child has theright to live, grow and develop and has the right to protection from violence anddiscrimination.” Child is the mandate at the same gift of Almighty God, which always shouldwe watch for in her inherent dignity, dignity, and rights as a human being which must beupheld. This paper analyzes the Constitution Court Decision No.46/PUU-VII/2010. Thedecision to make a breakthrough law for children born non-marital child. According toIndonesian civil law that non-marital child only have a legal relationship with his/herbiological mother, and according to the law number 1 of 1974 on Marriage that childrenborn non-marital child have a legal relationship with his/her biological mother dan his/her mother family. problem of this research, how are judge’s law paradigm in Decision No.46/PUU/VII/201. This research is the normative research, using the statutory approach, caseapproach and conceptual approaches. The main data is secondary data. Based on the resultsof the research thatThe judge’s paradigm in the constitutional court ruling is in contrast tothe Indonesian Civil Law and the law number 1 of 1974 on marriage. And according to theverdict non-marital child also has legal relationship with his/her biological father.